High dropout rate from aftercare program of antihepatitis C therapy for patients with history of injection drug use. Issue 5 (23rd June 2020) - Tamori, Akihiro; Uchida‐Kobayashi, Sawako; Kozuka, Ritsuzo; Motoyama, Hiroyuki; Yoshida, Kanako; Odagiri, Naoshi; Kotani, Kohei; Kawamura, Etsushi; Fujii, Hideki; Hagihara, Atsushi; Enomoto, Masaru; Kawada, Norifumi
Abstract: Background and Aim: We assessed direct‐acting antiviral (DAA) treatment for patients with hepatitis C virus (HCV) and a history of injection drug use (IDU) in Japan. Method: This retrospective observational study was based on clinical records. Overall, 804 DAA‐naïve HCV‐infected patients were enrolled, treated with a 12‐week regimen of DAAs, and had available information about a history of IDU. Anti‐HCV efficacy was defined as a sustained viral response 12 weeks post‐treatment (SVR12) only in patients who were assessed after 12 weeks [modified intention‐to‐treat (ITT) analyses]. We compared the antiviral effect between patients with (past‐IDU) and without a history of IDU (non‐IDU). We also evaluated the characteristics of each group, including the overall dropout rate and economic background. Results: Overall, 78 (9.7%) patients had a history of IDU. Compared to the non‐IDU group at baseline, the past‐IDU group consisted of predominantly male and younger patients infected with HCV genotype 2. Overall, 3% (3/78) and 16% (116/726) of the patients had cirrhosis in the past‐IDU and non‐IDU group, respectively. There was a significantly higher rate of welfare recipients in the past‐IDU group. SVR rate was 97% (59/61) in the past‐IDU group and 99% (689/699) in the non‐IDU group. The cumulative rate of dropout from an aftercare program was high in the past‐IDU group ( P < 0.01). Conclusions: DAAs had a remarkable anti‐HCV effect in patients with past‐IDU who continued in an aftercare program. It is necessary to understand the characteristics of past‐IDU patients to establish a support system for aftercare programs. Abstract : The cumulative dropout rates from the aftercare program of antihepatitis C therapy were significantly higher in the past‐IDU group compared to those in the non‐IDU group ( P < .01).